Design and losses analysis of a high power density machine for flooded pump applications - Al-Timimy, Ahmed; Giangrande, Paolo; Degano, Michele; Zeyuan, Xu; Galea, Michael; Gerada, C.; Lo Calzo, Giovanni; Zhang, He; Xia, Liqun (IEEE, 2018)
This paper describes the design process of a 10 kW 19000 rpm high power density surface mounted permanent magnet synchronous machine for a directly coupled pump application. In order to meet the required specifications, a compact machine, with cooling channels inside the slots and flooded airgap, has been designed through finite element optimization. For high power density, high speed machines, an accurate evaluation of the power losses and the electromechanical performance is always extremely challenging. In this case, the completely flooded application adds to the general complexity. Therefore this paper deals with a detailed losses analysis (copper, core, eddy current and mechanical losses) considering several operating conditions. The experimental measurements of AC copper losses as well as the material properties (BH curve and specific core losses), including the manufacturing process effect on the stator core, are presented. Accurate 3D finite element models and computational fluid dynamics analysis have been used to determine the eddy current losses in the rotor and windage losses respectively. Based on these detailed analysis, the no load and full load performance are evaluated. The experimental results, on the manufactured prototype, are finally presented to validate the machine design.